MASALAH WANPRESTASI PENGEMBANG APARTEMEN NEWTON RESIDENCE - Erica Khoirunnisa; Anda Setiawati (Fakultas Hukum Universitas Trisakti, 2021)
The practice of Pre-Project Selling is used by people in the construction of flats by binding potential buyers through a Sale and Purchase Agreement (PPJB). In reality, many problems arise, especially the problems in PPJB violations. The problems in this research are whether pre-project selling of Newton Residence Apartments is in accordance with applicable procedures and whether PPJB violations by the developer include acts of default or acts against the law and whether the consideration of the panel of judges stated that the perpetrators of the construction of defaults were in accordance with the provisions of the applicable law. To answer the problems, the authors conduct a normative and descriptive legal research by using secondary data obtained trough library research, analyzed qualitatively and the conclusions are drawn deductively. The results of this research are that the pre-project selling of Newton Residence Apartments is not in accordance with the Decree of Menpera No. 11/KPTS/1994 and the actions of the perpetrators of the development include acts of default in the form of not carrying out what has been agreed upon, and a court decision stating that the developer is default is in accordance with the applicable law and regulations.